A Narrative Review of Postoperative Anticoagulation Therapy for Congenital Cardiac Disease - Boucher, Alexander A.; Heneghan, Julia A.; Jang, Subin; Spillane, Kaitlyn A.; Abarbanell, Aaron M.; Steiner, Marie E.; Meyer, Andrew D. (Frontiers in Surgery, 2022)
Congenital heart disease encompasses a range of cardiac birth defects. Some defects require early and complex surgical intervention and post-operative thromboprophylaxis primarily for valve, conduit, and shunt patency. Antiplatelet and anticoagulant management strategies vary considerably and may or may not align with recognized consensus practice guidelines. In addition, newer anticoagulant agents are being increasingly used in children, but these medications are not addressed in most consensus statements. This narrative review evaluated the literature from 2011 through 2021 on the topic of postoperative thromboprophylaxis after congenital heart disease operations. The search was focused on the descriptions and results of pediatric studies for replacement and/or repair of heart valves, shunts, conduits, and other congenital heart disease operations. Wide variability in practice exists and, as was true a decade ago, few randomized controlled trials have been conducted. Aspirin, warfarin, and perioperative heparin remain the most commonly used agents with varying dosing, duration, and monitoring strategies, making comparisons difficult. Only recently have data on direct oral anticoagulants been published in children, suggesting evolving paradigms of care. Our findings highlight the need for more research to strengthen the evidence for standardized thromboprophylaxis strategies.